Physical characterization of biphasic bioceramic materials with different granulation sizes and their influence on bone repair and inflammation in rat calvaria - Joviniano Martins de Oliveira Junior (Nature Portfolio, 2021)
Abstract Biphasic calcium phosphate bioceramics (BCP) consist of a mixture of hydroxyapatite (HA) and beta-tricalcium phosphate (β-TCP) within the same particle. Due to their osteoconductive properties, biocompatibility and resemblance to natural bone, these materials have become a promising and suitable alternative to autologous bone grafting. First, the topography characteristics, specific surface area, and total pore volume of BCP were evaluated using scanning electron microscopy and the BET and BJH methods. Next, this study aimed to evaluate the intensity of the inflammatory process and the bone neoformation capacity of various particle sizes of BCP in the repair of critical defects in the calvaria of rats. A xenogeneic biomaterial was used in the control group. After 30, 60, and 90 days, the animals were euthanized, followed by the processing of the samples to measure the intensity of inflammatory infiltrates and the areas of bone neoformation. Our results indicate that no considerable differences were observed in the inflammatory scores in sites treated with distinct BCP grain sizes. A greater area of bone neoformation was measured in the xenogeneic group at all analysis times, with no substantial differences in bone formation between the BCP particle size in the range of 250–500 µm and 500–1000 µm.